Metodologia para análise de aspectos urbanísticos e sustentáveis: estudo de caso de loteamentos novos do município de Dois Vizinhos - Martinazzo, Daise (2019)
The disordered growth of several cities and their territorial expansions started the conceptual discussion about urban sprawl, as occurs in the municipality of Dois Vizinhos - PR. It is observed that there has been a great growth of the urban network in the last years, thus, having the diligence to verify which peculiarities are attributed in the execution of the urban expansion. This work presents a diagnosis from the spatial and temporal delimitation to verify the growth of the urban spot. For this diagnosis it was decided to delimit three new lots approved after 2012 and a neighborhood from the beginning of the colonization of the municipality in 1953. In addition, some urban and sustainable aspects are analyzed, such as: width and continuity of roads and sidewalks, landscape, destination of institutional areas and declivity. Thus, the study proposes and presents a methodology to define sustainability and urban indicators, created from the integration of information obtained and geospatial data, norms, laws and literatures (technical aspects), in order to allow a qualitative analysis aspects of urban sprawl. In addition to the on-site collection, ArcGis 10.0 software was also used for integration, data manipulation and thematic map generation. After this step two methods were applied to quantify and assign weights in the sustainable and urbanistic criteria, allowing to verify the consistency of the qualitative analysis through the normalization of data: the fuzzy method and the hierarchical analytical process AHP. In sequence, the results were presented in graph form to verify which criteria of the indicators created are met in the lots. Observing that the growth of the city is ordered and complies with the legislation, in contrast, it was noticed that the dimensions do not present good functionality. One of the great debates in the current expansion is the sustainable growth, which was evidenced that must be revised and inserted in the planning of the municipality.